Recessive Dystrophic Epidermolysis Bullosa: Rare Bilateral External Auditory Canal Stenosis and Surgical Treatment. Issue 15 (December 2022) - Milani, Alessandro; Pace, Annalisa; Iannella, Giannicola; Corsi, Alessandro; Cocuzza, Salvatore; Maniaci, Antonino; Greco, Antonio; Magliulo, Giuseppe
Epidermolysis bullosa (EB) is a family of rare genetic disorders affecting the skin and mucous membranes, causing blisters and lesions. Its treatment is based on the prevention of traumatic events that could favor the onset of blisters as well as careful wound care. New therapies, including gene therapy, are under investigation. In the case described here, a rare localization of EB at the level of the ear canal is described. To our knowledge, no surgical option for treatment has previously been described in the literature. The clinical features observed and the therapeutic modalities adopted are presented and discussed. A 56-year-old female patient came to our attention for bilateral progressive hearing loss. The patient was suffering from Dystrophic EB. Surgical correction of the stenosis through a retroauricular approach was planned, with the simultaneous reconstruction of the right external auditory canal using the canaloplasty technique combined with Thiersch skin grafting. The case we report here is, to our knowledge, the second describing the surgical treatment of ear canal stenosis secondary to EB. As a result of surgical correction of the stenosis, the ear regained its physiological function and there was an improvement in hearing. In the subsequent post-operative controls, there was no recurrence of the disease, from which the patient is still free 36 months after surgery. Although conservative treatment is a solid choice, our experience seems to indicate that the surgical option allows better management of the Dystrophic EB in the external auditory canal.